Evaluación de la espiculectomía peneana en cobayos (cavia porcellus) como método de castración ancestral en el cantón Saquisilí barrió la Libertad. - Martínez Quintana, Carmen Elina (2020)
This research was carried out in the province of Cotopaxi, Saquisilí Canton La Libertad neighborhood. The main objective of the research was the evaluation of penile spiculectomy as an ancestral castration method, verifying if ancestral castration works in guinea pigs, evaluating the variables such as pregnancy, testosterone levels, and spicule growth. For this investigation, 60 nonpregnant female guinea pigs and six male guinea pigs were used in adulthood, doing the investigation as the first group T0 30 female guinea pigs distributed in six cages on the floor; 5 nonpregnant females and a male (without castration) in this first treatment gave a result of 4 and 5 pregnant guinea pigs in each cage to detect pregnancy. An ultrasound was used for better results. In the second group T1, we used the same procedure as in T0, which were equally distributed in 6 cages each one with six guinea pigs; 5 nonpregnant female guinea pigs and the same male of the T0 treatment were located in each cage, but this time the spicules were removed (castration), assessing the two levels of testosterone that each of them possesses. Before and after castration, in the previous group, the number of pregnancies in guinea pigs was also assessed by an ultrasound with a frequency of 2.5 to 7 in which there was a pregnancy but in a lower amount of pregnancy in them, obtaining in each cage from 2 to 3 pregnant animals with the neutered male. With this research the result was the existence of pregnancy in guinea pigs, but in smaller quantities, they obtain a good weight and also lowering their testosterone level.